EXPLORING CODE-SWITCHING IN ENGLISH LANGUAGE CLASSROOMS: TEACHER PERSPECTIVES AND IMPLICATIONS FOR STUDENT ENGAGEMENT - Muhammad Ihsan; Baso Jabu; Muhammad Tahir (State University of Makassar, 2026)
This study examines how the role and position of code switching in English language learning at SMP Negeri 3 Parepare, focusing on teachers' perceptions of code switching and the role of code switching in students' involvement in teaching. The approach is done with qualitative research method; data collection is done by observation in the classroom and interviews to several English teachers and students taught by the teacher. Based on the data obtained from the interviews, which showed a dominant positive attitude towards code switching and hope for the potential of code switching in the future. In addition, observation data showed the role of code switching in student engagement and activeness which increased when it was used. After conducting interviews as a follow-up to observations, many students and teachers indicated that code switching can increase students' comfort and motivation in learning English because they feel they can be accepted in the “English only” system that is often used in English language learning now, even so what concerns teachers is the frequency of its use which must be paid more attention to in order to be more effective. From the research conducted, it can be concluded that code-switching plays an important role in the English language learning process. The use of code-switching as a pedagogical strategy bridge understanding and maintains student engagement in the classroom, while students are assisted in terms of material comprehension, emotional comfort, and active participation. However, both teachers and students are aware that excessive reliance on the mother tongue can hinder the development of English-speaking skills. Therefore, the effectiveness of code-switching depends on its measured, purposeful, and contextual application, so that it can function as a flexible and effective learning tool, not something that is overused or completely rejected.Keywords: Code switching, Student engagement, language learning, Pedagogic, Teacher perception.